Homocysteine levels in amniotic fluid - Grandone, Elvira; Colaizzo, Donatella; Vecchione, Gennaro; Sciannamè, Natale; Notarangelo, Angelo; Croce, Anna Irma; Margaglione, Maurizio (Thrombosis and Haemostasis, 2006)
Hyperhomocysteinemia could playa similar role in the placenta to that played in adults at risk of thrombosis. Moreover, hyperhomocysteinemia in women is described to be associated with the birth of small for gestational age (SGA) newborns, although there are discrepancies on this issue. To date, there is no biochemical marker predictive of SGA in a given pregnancy. We verified the presence of a relationship between homocysteine in amniotic fluid at mid-pregnancy and birth-weight. Amniotic fluid was obtained from 459 healthy women undergoing midtrimester amniocentesis (17.1 ± 1.2 weeks) because of maternal age. Homocysteine levels were measured in 434 (10 twin) pregnancies. In addition, femur length (FL) and biparietal diameter (BPD) were measured. Outcome of pregnancy was recorded. 233 (53.7%) foetuses were males,201 (46.3%) females. The mean homocysteine concentration was 1.04 ± 0.72 µM, (95% C.I. 0.43–2.41). An univariate analysis showed the presence of an association with gestational age, FL, BPD. A multiple linear regression showed that homocysteine levels were significantly associated with FL (p<0.001) and BPD (p=0.011). After excluding twin pregnancies, 31 newborns (7.3%) were classified as SGA. Mean birth-weight was 2390 g in SGA, where as it was 3360 g in 393 adequate for gestational age (AGA) newborns (p<0.001).The adjusted mean level of homocysteine was significantly lower in AGA (1.01 µM; 95%CI: 0.94–1.08) than that recorded in pregnancies resulting in a SGA (1.29 µM; 95%CI: 1.05–1.51; p=0.03). In a large setting, these data provide reference values for homocysteine in amniotic fluids. Moreover, they suggest that homocysteine levels in amniotic fluids may be higher in pregnancies with a SGA newborn.
Keywords: Homocysteine; amniotic fluid; foetal growth; prenatal diagnosis